2020
DOI: 10.3390/en13040809
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Time-Frequency Characteristics of Microseismic Signals in the Damage Evolution Process of Coal and Rock

Abstract: The deformation and failure of coal and rock materials is the primary cause of many engineering disasters. How to accurately and effectively monitor and forecast the damage evolution process of coal and rock mass, and form a set of prediction methods and prediction indicators is an urgent engineering problems to be solved in the field of rock mechanics and engineering. As a form of energy dissipation in the deformation process of coal and rock, microseismic (MS) can indirectly reflect the damage of coal and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…where k = 1, 2, 3, …, n À 1, argmin is defined as the global minimum. Yang et al 43 modified the above method based on whether there was a local minimum before the global minimum and believed that if there was local minimum, the first minimum would be taken as the cut-off point. If the local minimum did not exist, the global minimum point was used as the cut-off point.…”
Section: Data Processing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…where k = 1, 2, 3, …, n À 1, argmin is defined as the global minimum. Yang et al 43 modified the above method based on whether there was a local minimum before the global minimum and believed that if there was local minimum, the first minimum would be taken as the cut-off point. If the local minimum did not exist, the global minimum point was used as the cut-off point.…”
Section: Data Processing Methodsmentioning
confidence: 99%
“…However, frequency domain analysis can screen out the real EMR signals and play a vital role in improving the accuracy of EMR prediction. Most researchers use Fourier analysis, wavelet analysis, and empirical mode decomposition (EMD) methods to reduce noise and achieve good results 31,39,43 . The EMR induced from deformation and fracture of coal and rock is broadband, and many researchers have found that the frequency of EMR ranges from DC/ULF to VHF (or even higher) through studies on different coal and rock materials in different observation scales 44,45 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal is an indispensable conventional energy in many countries and regions. Ensuring safe mining and efficient operation of coal mines has always been the long-term goal of the coal industry. , The complex geological environment and tectonic movement of the coal seam determine that the underground coal seam mining process will face potential risks such as water inrush, rockburst, gas outburst, and coal dust explosion. , In China, coal consumption still constitutes 65% of total primary energy consumption . In recent years, there has been a notable escalation in the depth and intensity of coal mining operations, further elevating the likelihood of mine disasters such as rockbursts …”
Section: Introductionmentioning
confidence: 99%
“…In terms of AE signals, AE counts (Kong et al., 2019), AE energy (Tian et al., 2021), and AE entropy (Yang et al., 2021) were used to obtain damage curves for rock specimens during loading, and their damage variables showed a very consistent trend. In terms of MS signals, a damage equation was established by using MS events in coal rock damage evolution (Yang et al., 2020). However, in terms of sound signals, the evaluation of rock damage progression has rarely been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%